Pengembangan Instrumen Self Assessment pada Praktik Menjahit Rok Berfuring - Budiastuti, Emy; Karomah, Prai; Fatmawati, Diah (Jurnal Pendidikan Teknologi dan Kejuruan, 2014)
The objectives of the study were to develop a self assessment instrument, its specific characteristics and its procedure and to analyse the consistency between the assessment of the students and the lecturer. This study was a research and development (R and D) using the R and D model offered by Borg and Gall. The samples of this study were 32 students who took the course of Fashion Technology II. They were selected with purposive sampling. The methods of data collection consisted of assessment sheets, rubrics, assessment procedures and scoring. The instrument used the content validity based on expert judgment and inter-rater reliability. The results of this study were: (1) The developed self assessment instruments that consist of the assessment sheets and the rubrics; (2) the assessment procedure was developed starting from the socialisation instrument and the observation instrument while the self assessment was started from preparation to results; (3) the consistency between the assessment of the students and the lecturer was rated by the Kappa coefficient of 0.69